Transverse abdominis plane block under different guidance in laparoscopic cholecystectomy: anatomy and technique, systematic review and double meta-analysis - S.M. Chooklin; S.S. Chuklin; R.V. Barylyak (Медицина неотложных состояний)
Background. Postoperative pain following laparoscopic cholecystectomy remains a significant clinical issue. Laparoscopic (L-TAPB) and ultrasound-guided transverse abdominis plane block (US-TAPB) are widely used for postoperative analgesia in laparoscopic cholecystectomy. However, their comparative effectiveness remains a subject of debate. Materials and methods. A systematic search for randomized controlled trials published up to January 2025 that compared TAPB under ultrasound and laparoscopic guidance was performed in PubMed, Scopus, and Cochrane databases. The outcomes evaluated included the intensity of postoperative pain using the visual analogue scale, duration of surgery, time to the first analgesic requirement, postoperative morphine consumption, frequency of postoperative nausea and vomiting (PONV), time to first flatus, and time to first bowel evacuation. The risk of bias was assessed using the Cochrane Risk of Bias tool (RoB-2), and statistical analysis was performed using IBM SPSS Statistics 30.0 software. Results. Ten randomized controlled trials were included in the analysis. L-TAPB effectively reduces the intensity of postoperative pain after laparoscopic cholecystectomy, delaying the need for additional analgesia. However, this effect was not observed six hours post-surgery. Other parameters studied, such as PONV frequency and time to bowel function recovery, did not show statistically significant changes. At the same time, no statistically significant differences were observed between L-TAPB and US-TAPB regarding pain intensity at 1, 6, 12, and 24 hours postoperatively, duration of surgery, time to the first analgesic requirement, postoperative morphine consumption, PONV frequency, time to first flatus, and time to first bowel evacuation. L-TAPB, performed at the beginning of the surgery, more effectively reduces the intensity of postoperative pain. The analysis showed significant heterogeneity of studies, but overall low risk of bias in assessing their quality. Conclusions. This meta-analysis confirmed the effectiveness of L-TAPB in alleviating postoperative pain and associated factors after laparoscopic cholecystectomy. However, it did not demonstrate any advantage of US-TAPB over L-TAPB in managing postoperative pain. Further randomized clinical trials are required to validate and support these findings.